Polyhedral oligomeric silsesquioxane (POSS)-containing bismaleimide-based single-ion conductor polymer electrolyte membrane and preparation method thereof
By preparing a POSS-containing bismaleimide single-ion conductor polymer electrolyte membrane, the problems of instability of liquid electrolytes and low ion conductivity of solid electrolytes in lithium-ion batteries are solved, and high lithium ion migration number and good battery cycling performance are achieved.
Patent Information
- Application Number
- CN202510674350.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-05-23
- Publication Date
- 2025-08-29
AI Technical Summary
The liquid electrolytes of existing lithium-ion batteries are unstable, volatile and flammable, and the room temperature ionic conductivity of traditional solid electrolytes is low, and the lithium dendrites problem has not been effectively solved, which limits the development and application of lithium metal batteries.
A bismaleimide monoion conductor polymer electrolyte membrane containing POSS was prepared by chemical reaction, and a polymer film with a cross-linking network structure was constructed with POSS and ethylene carbonate containing methacrylic acid structure was constructed by ultraviolet light-induced radical copolymerization.
The number of lithium ion migration and room temperature ion conductivity are improved, the flexibility of the electrolyte and the compatibility of the electrode-electrolyte interface are enhanced, the risk of lithium dendrites is reduced, and the safety and circulation performance of the battery are improved.
Smart Images

Figure CN120554686A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of polymer electrolytes, in particular to a bismaleimide-based single-ion conductor polymer electrolyte membrane containing POSS and a preparation method thereof. Background Art
[0002] With the development of science and technology and the enhancement of environmental protection awareness, renewable energy will gradually replace fossil energy and become the main energy source. Lithium-ion batteries have become a promising energy candidate due to their energy density and durability. At present, commercial lithium-ion batteries mainly use graphite (C) as the negative electrode material, which is close to its theoretical energy density (390Whkg -1 ), but it cannot meet people’s demand for high energy density energy storage devices. Lithium metal has a high energy density (3860mAh g -1 ) and low potential (-3.04 V relative to standard hydrogen electrode) have gradually become research hotspots in recent years.
[0003] However, the liquid electrolytes used in conventional lithium metal batteries are chemically unstable, volatile, flammable, and explosive. Furthermore, they are unable to suppress the formation of lithium dendrites during the lithium deposition / dissolution process, which can easily lead to safety issues and thus limit the further promotion and application of high-energy-density lithium metal batteries. Solid-state electrolytes have excellent mechanical properties and thermal stability, which can, to a certain extent, slow the penetration and puncture of lithium dendrites through the separator, reducing the risk of lithium battery short circuits, explosions, and combustion. However, traditional solid-state electrolytes have disadvantages such as low room-temperature ionic conductivity, low lithium ion transference number, and high interface impedance with the positive and negative electrodes.
[0004] The use of single-ion conducting polymer electrolytes can effectively increase the lithium ion transference number and provide good flexibility and designability. However, their low room-temperature ionic conductivity limits their development and practical application. Improving the room-temperature ionic conductivity and various performance of single-ion conducting polymer electrolytes is one of the most pressing research issues. Summary of the Invention
[0005] In view of this, an object of the present invention is to provide a bismaleimide-based single-ion conductor polymer electrolyte membrane containing POSS and a preparation method thereof.
[0006] The object of the present invention is achieved through the following technical solutions:
[0007] <First Aspect>
[0008] The present invention provides a single ion conductor monomer, the structural formula of which is:
[0009]
[0010] <Second Aspect>
[0011] The present invention provides a method for preparing the above-mentioned single ion conductor monomer, comprising the following steps:
[0012] The intermediate I and maleic anhydride are dissolved in a third solvent, reacted at 20-30° C. for 25-35 minutes, and then sodium hydroxide and acetic anhydride are added and reacted at 60-80° C. After the reaction is completed, ethyl acetate is added to produce a precipitate, and the precipitate is extracted to obtain the single ion conductor monomer. The intermediate I has the structural formula:
[0013]
[0014] As an embodiment, the molar ratio of the intermediate I, maleic anhydride, sodium hydroxide and acetic anhydride is 1:(2-3):(0.2-0.5):(6-7).
[0015] In some embodiments, the molar ratio of the intermediate I, maleic anhydride, sodium hydroxide, and acetic anhydride is 1:2:0.3:6.
[0016] In some embodiments, the third solvent is N,N-dimethylacetamide.
[0017] In some embodiments, the preparation method of the single-ion conductor monomer is: dissolving intermediate I and maleic anhydride in a third solvent, reacting at room temperature for 30 minutes, adding sodium hydroxide and acetic anhydride, and reacting at 75°C. After the reaction is completed, adding ethyl acetate to produce a precipitate, and extracting the precipitate to obtain the single-ion conductor monomer.
[0018] As an embodiment, the preparation method of the intermediate I is:
[0019] Dissolve p-nitrobenzenesulfonamide and lithium hydroxide in a first solvent, add p-nitrobenzenesulfonyl chloride at -5 to 5°C, allow to react fully, and extract the intermediate product;
[0020] The intermediate product, palladium carbon catalyst and ferric chloride are dissolved in a second solvent, hydrazine hydrate is added at 60-80° C., and the temperature is maintained for reflux reaction for 3.5-4.5 hours, and the product is extracted to obtain the intermediate I.
[0021] As an embodiment, the molar ratio of the three substances, p-nitrobenzenesulfonamide, p-nitrobenzenesulfonyl chloride and lithium hydroxide, is 1:(1-1.2):(3-3.5).
[0022] In some embodiments, the molar ratio of the p-nitrobenzenesulfonamide, p-nitrobenzenesulfonyl chloride and lithium hydroxide is 1:1:3.
[0023] As an embodiment, the usage ratio of the four substances, namely, p-nitrobenzenesulfonamide, palladium-carbon catalyst, ferric chloride, and hydrazine hydrate, is 10 g: (1-2) g: (0.5-2) g: (25-30) mL.
[0024] In some embodiments, the usage ratio of the four substances, namely, p-nitrobenzenesulfonamide, palladium-carbon catalyst, ferric chloride, and hydrazine hydrate, is 10.1 g:1.5 g:1 g:30 mL.
[0025] In some embodiments, the first solvent is acetone.
[0026] In some embodiments, the second solvent is anhydrous ethanol.
[0027] In some embodiments, the preparation method of the intermediate I is:
[0028] Dissolve p-nitrobenzenesulfonamide and lithium hydroxide in a first solvent, add p-nitrobenzenesulfonyl chloride at 0°C, allow to react fully, and extract the intermediate product;
[0029] The intermediate product, palladium carbon catalyst and ferric chloride are dissolved in a second solvent, hydrazine hydrate is added at 70° C., and the temperature is maintained to carry out reflux reaction for 4 hours, and the product is extracted to obtain the intermediate I.
[0030] <Third Aspect>
[0031] The present invention provides a method for preparing a bismaleimide-based single-ion conductor polymer electrolyte membrane containing POSS, comprising the following steps:
[0032] S1, preparing a precursor solution I containing POSS and vinyl ethylene carbonate, and a precursor solution II containing poly(vinylidene fluoride-hexafluoropropylene) and a single ion conductor monomer;
[0033] S2, mixing the precursor solution I and the precursor solution II, adding a photoinitiator, and stirring at 20-30° C. to obtain a uniform slurry;
[0034] S3, coating the slurry on a substrate, irradiating with ultraviolet light to initiate free radical polymerization, and drying to obtain an initial electrolyte membrane;
[0035] S4. Fully immersing the initial electrolyte membrane in an electrolyte solution to obtain the electrolyte membrane.
[0036] In some embodiments, the POSS is an isobutyl methacrylate-type polyhedral oligomeric silsesquioxane.
[0037] As an embodiment, the mass ratio of the single ion conductor monomer, POSS, vinyl ethylene carbonate, poly(vinylidene fluoride-hexafluoropropylene) and photoinitiator is 10:(0.5-2.2):(10-15):(5-7):(0.2-0.5).
[0038] As an embodiment, the mass ratio of the single ion conductor monomer, POSS, vinyl ethylene carbonate, poly(vinylidene fluoride-hexafluoropropylene) and photoinitiator is 10:(0.5-1):(10-15):(5-7):(0.2-0.5).
[0039] In some embodiments, the mass ratio of the single ion conductor monomer, POSS, vinyl ethylene carbonate, poly(vinylidene fluoride-hexafluoropropylene) and photoinitiator is 10:0.5 to 2:12:6.5:0.3.
[0040] In some embodiments, the mass ratio of the single ion conductor monomer, POSS, vinyl ethylene carbonate, poly(vinylidene fluoride-hexafluoropropylene) and photoinitiator is 10:1:12:6.5:0.3.
[0041] As an embodiment, the solvent in the precursor solution I or the precursor solution II is one or more of N,N-dimethylformamide, N,N-dimethylacetamide, N-methylpyrrolidone, isopropyl alcohol, and tetrahydrofuran.
[0042] In some embodiments, the solvent in the precursor solution I is isopropyl alcohol.
[0043] In some embodiments, the solvent in the precursor solution II is N,N-dimethylformamide.
[0044] As an embodiment, the photoinitiator is one or more of 2-hydroxy-2-methyl-1-phenyl-1-propanone, benzoin diethyl ether, and benzoin dimethyl ether.
[0045] In some embodiments, the photoinitiator is 2-hydroxy-2-methyl-1-phenyl-1-propanone.
[0046] As an embodiment, the ultraviolet irradiation is irradiation under 365nm ultraviolet light for 8 to 15 minutes.
[0047] In some embodiments, the ultraviolet irradiation time is 10 minutes.
[0048] In some embodiments, the electrolyte is EC / V DEC =1 / 1 configuration of electrolyte.
[0049] <Fourth Aspect>
[0050] The invention provides a bismaleimide-based single ion conductor polymer electrolyte membrane containing POSS, which is prepared by adopting the method.
[0051] As an embodiment, the electrolyte membrane has a lithium ion transference number of 0.71 to 0.80 and a lithium ion transference number of 0.68 to 1.60×10 -4 S cm -1 Room temperature ionic conductivity.
[0052] In some embodiments, the electrolyte membrane has a lithium ion transference number of 0.80 and a -4 S cm -1 Room temperature ionic conductivity.
[0053] Compared with the prior art, the present invention has the following beneficial effects:
[0054] 1) The present invention provides a method for preparing a bismaleimide-based single-ion conductor polymer electrolyte membrane containing POSS. First, a bis-4-maleimide benzenesulfonyl imide lithium salt monomer is prepared through a series of chemical reactions, and then the monomer is copolymerized with POSS containing a methacrylic acid structure and vinyl ethylene carbonate through ultraviolet light-induced free radicals to construct a polymer membrane with a cross-linked network structure, thereby solving the problem that the ionic conductivity of the single-ion conductor polymer electrolyte is significantly lower than that of traditional double-ion electrolytes.
[0055] 2) The single-ion conductor monomer provided in the present invention can be polymerized with POSS containing a methacrylic acid structure and vinyl ethylene carbonate through ultraviolet light-induced free radical polymerization to obtain a polymer membrane with a cross-linked network that can quickly conduct lithium ions. This can effectively improve the ionic conductivity and lithium ion transference number of the polymer electrolyte. The electrolyte has a wide electrochemical window and good electrode-electrolyte interface compatibility. The lithium metal battery assembled with the electrolyte has good cycle performance and can stably cycle for more than 300 cycles at 0.5C.
[0056] 3) The electrolyte membrane provided in the present invention has high safety and low production cost, high lithium ion transference number and room temperature ionic conductivity, and has the potential for practical production application. BRIEF DESCRIPTION OF THE DRAWINGS
[0057] Other features, objects and advantages of the present invention will become more apparent upon reading the detailed description of non-limiting embodiments with reference to the following drawings:
[0058] Figure 1 This is a hydrogen nuclear magnetic resonance spectrum of the single ion conductor monomer Li-BMBSI prepared in Example 2 of the present invention;
[0059] Figure 2This is an electrochemical test diagram of the electrolyte membrane prepared in Example 2 of the present invention, wherein: Figure 2 (a) is the AC impedance spectrum, Figure 2 (b) is the polarization curve, Figure 2 (b) Inset is the initial, steady-state impedance diagram. DETAILED DESCRIPTION
[0060] The present invention will be described in detail below with reference to the examples. The following examples will help those skilled in the art to further understand the present invention, but are not intended to limit the present invention in any form. It should be noted that those skilled in the art may make several adjustments and improvements without departing from the scope of the present invention. These all fall within the scope of protection of the present invention.
[0061] For ease of understanding, the abbreviations or nouns mentioned below are first explained:
[0062] POSS: polyhedral oligomeric silsesquioxane. In the present invention, isobutyl methacrylate type polyhedral oligomeric silsesquioxane is selected, and the monomer structure is:
[0063]
[0064] Li-BMBSI: lithium bis(4-maleimidobenzenesulfonyl)imide;
[0065] PVDF-HFP: poly(vinylidene fluoride-hexafluoropropylene), average molecular weight 400,000;
[0066] VEC: vinyl ethylene carbonate;
[0067] HMPP: 2-hydroxy-2-methyl-1-phenyl-1-propanone;
[0068] DMAc: N,N-dimethylacetamide;
[0069] DMF: N,N-dimethylformamide.
[0070] First, a method for preparing a single ion conductor monomer is introduced through Example 1.
[0071] Example 1
[0072] A method for preparing a single ion conductor monomer (Li-BMBSI), the specific steps are as follows:
[0073] 20.2 g (0.1 mol) of p-nitrobenzenesulfonamide and 7.18 g (0.3 mol) of lithium hydroxide were dissolved in acetone, and 22.2 g (0.1 mol) of p-nitrobenzenesulfonyl chloride was added at 0°C. The mixture was reacted at 0°C for 48 hours. After the reaction was completed, the reaction solution was filtered and rotary evaporated to obtain a yellow solid.
[0074] The yellow solid was dissolved in anhydrous ethanol, 3 g of palladium carbon catalyst and 2 g of ferric chloride were added, and 60 mL of hydrazine hydrate was slowly added dropwise at 70°C. After the addition was completed, the mixture was refluxed at 70°C for 4 hours. After the reaction was completed, the reaction solution was filtered and rotary evaporated. The obtained solid was washed three times with ethyl acetate and dried at 70°C to obtain a white powder, which is Intermediate I. The structural formula is as follows:
[0075]
[0076] 33.4 g (0.1 mol) of intermediate I and 19.6 g (0.2 mol) of maleic anhydride were dissolved in DMAc and reacted at room temperature for 30 minutes. 1.2 g (0.03 mol) of sodium hydroxide and 56 mL (0.6 mol) of acetic anhydride were added and dehydrated at 75 ° C for 2 hours. After the reaction was completed, the reaction solution was cooled and a large amount of ethyl acetate was added to obtain a brown-black precipitate. The product was filtered and washed three times with ethyl acetate and dried at 70 ° C to obtain a brown-black solid powder, which was a single ion conductor monomer (Li-BMBSI).
[0077] It should be noted that:
[0078] During the steps, 0°C was controlled by means of an ice-water bath;
[0079] In the step, hydrazine hydrate is slowly added dropwise, and the dropping rate is controlled to be 5 to 10 seconds per drop through a constant pressure dropping funnel.
[0080] In this example, the amounts of acetone, anhydrous ethanol, DMAc, and other solvents involved should, in principle, be sufficient to completely dissolve the reactants. The amounts used were 250 mL, 600 mL, and 200 mL, respectively.
[0081] The H NMR spectrum of Li-BMBSI is as follows Figure 1 As shown, the molecular structure of Li-BMBSI is determined as follows:
[0082]
[0083] The monomer is named as bis-4-maleimide benzenesulfonyl imide lithium salt monomer, which belongs to the benzenesulfonyl imide lithium salt monomer with bismaleimide structure.
[0084] Next, a method for preparing an electrolyte membrane using the above-mentioned single ion conductor monomer is introduced.
[0085] Example 2
[0086] A method for preparing a bismaleimide-based single-ion conductor polymer electrolyte membrane containing POSS, comprising the following steps:
[0087] Isobutyl methacrylate type polyhedral oligomeric silsesquioxane POSS and VEC were added to isopropyl alcohol and dissolved to obtain precursor solution I;
[0088] PVDF-HFP and Li-BMBSI were added into DMF solvent and dissolved to obtain precursor solution II;
[0089] After the precursor solution I and the precursor solution II are evenly mixed, the photoinitiator HMPP is added and stirred at room temperature to obtain a uniform slurry;
[0090] The slurry was evenly coated on a glass plate and irradiated with 365 nm ultraviolet light for 10 min to initiate free radical polymerization. The initial electrolyte membrane was obtained after drying at 70 °C and then heated to 40 °C. EC / V DEC = 1 / 1 electrolyte for 15 minutes and then taken out to obtain a bismaleimide-based single-ion conductor polymer electrolyte membrane containing POSS, which can be used to assemble into a battery.
[0091] In this embodiment, the mass ratio of Li-BMBSI, POSS, VEC, PVDF-HFP and initiator is 10:1:12:6.5:0.3, the amount of isopropanol is 20 times the mass of Li-BMBSI, and the amount of DMF is 50 times the mass of Li-BMBSI.
[0092] Example 3
[0093] A method for preparing a bismaleimide-based single-ion conductor polymer electrolyte membrane containing POSS, the steps are basically the same as those in Example 2 above, except that:
[0094] In this embodiment, the mass ratio of Li-BMBSI, POSS material, VEC, PVDF-HFP and initiator is: 10:0.5:12:6.5:0.3.
[0095] Example 4
[0096] A method for preparing a bismaleimide-based single-ion conductor polymer electrolyte membrane containing POSS, the steps are basically the same as those in Example 2 above, except that:
[0097] In this embodiment, the mass ratio of Li-BMBSI, POSS material, VEC, PVDF-HFP and initiator is: 10:2:12:6.5:0.3.
[0098] Comparative Example 1
[0099] A method for preparing a bismaleimide-based single-ion conductor polymer electrolyte membrane without POSS, the steps of which are basically the same as those of Example 2 above, except that:
[0100] In the step, the precursor solution I does not contain POSS material but only contains VEC. After soaking in the electrolyte, a bismaleimide-based single ion conductor polymer electrolyte membrane without POSS is obtained.
[0101] Comparative Example 2
[0102] A method for preparing a dual ion conductor polymer electrolyte membrane containing POSS, the steps are basically the same as those of the above embodiment 4, except that:
[0103] The Li-BMBSI in the step is replaced with an equal amount of lithium bis(trifluoromethanesulfonyl)imide. After being immersed in an electrolyte, a dual ion conductor polymer electrolyte membrane containing POSS is obtained.
[0104] Application performance testing:
[0105] The electrolyte membranes prepared in Examples 2 to 4 and Comparative Examples 1 to 2 were assembled into steel sheet|electrolyte|steel sheet CR2016 button cells, respectively. 6 Hz~0.1Hz, AC impedance test is carried out at 25℃ and 75℃, according to the formula Calculate its ionic conductivity, where σ is the ionic conductivity; L is the thickness of the electrolyte membrane, and the thickness of the prepared electrolyte membrane is in the range of 60-80 μm; S is the steel sheet electrode area, which is 2.06 cm 2 ; R is the resistance of the electrolyte membrane.
[0106] The AC impedance spectrum, polarization curve, initial and steady-state impedance diagrams of the electrolyte membrane prepared in Example 2 are shown in Figure 2. Figure 2 shown.
[0107] The electrolyte membranes prepared in Examples 2 to 4 and Comparative Examples 1 to 2 were assembled into lithium sheet|electrolyte|lithium sheet CR2032 button cells, respectively. The current and AC impedance of the cells before and after polarization were measured using the Bruce-Vincent-Evans method at room temperature. According to the formula Calculate the lithium ion migration number, where t Li + is the lithium ion transfer number, ΔV is the polarization voltage, I0 is the initial current, I ss is the steady-state current, R0 is the impedance before polarization, R ss is the impedance after polarization.
[0108] The electrolyte membranes prepared in Examples 2 to 4 and Comparative Examples 1 to 2 were respectively assembled into lithium sheet|electrolyte|steel sheet CR2025 button batteries, and linear sweep voltammetry tests were performed at room temperature with the starting voltage set to 0 V, the ending voltage set to 7 V, and the scan rate set to 0.01 V / s.
[0109] The electrolyte membranes prepared in Examples 2 to 4 and Comparative Examples 1 to 2 were respectively assembled into Li|electrolyte|LiFePO4 batteries, and cycle performance tests were performed on a LAND CT2001A test system at 25°C with a set voltage range of 2.5-4V and a current density of 0.5C.
[0110] The test results of various embodiments and comparative examples are shown in Table 1.
[0111] Table 1 Performance test results of electrolyte membranes corresponding to Examples 2 to 4 and Comparative Examples 1 to 2
[0112]
[0113] Compared with the comparative example, the ionic conductivity of Examples 2 to 3, the lithium ion transference number, the electrochemical window, the cycle number and other performance of Examples 2 to 4 are significantly improved.
[0114] In sum, the bismaleimide-based single ion conductor polymer electrolyte containing POSS prepared in embodiments of the present invention 2 to 4 has higher lithium ion migration number compared to traditional double ion polymer electrolyte. This is because the spatial impedance effect formed by the POSS cage structure has suppressed the migration of bulk anions, also can improve interfacial compatibility, strengthen ion transport capability. Simultaneously, the POSS cage structure can be used as a plasticizer, reduces the crystallinity of electrolyte, improves the activity of polymer chain, thereby improves the ionic conductivity of electrolyte.
[0115] A high lithium-ion transference number can suppress polarization caused by anion movement during the cycling of lithium-ion batteries and reduce the occurrence of battery side reactions, thereby achieving uniform lithium deposition and inhibiting lithium dendrite growth. The introduction of a POSS structure can also improve the thermodynamic stability of the polymer electrolyte, reduce the electrode-electrolyte interface impedance, and achieve more stable battery cycling.
[0116] The above describes the specific embodiments of the present invention. It should be understood that the present invention is not limited to the above specific embodiments, and those skilled in the art may make various variations or modifications within the scope of the claims, which do not affect the essence of the present invention.
Claims
1. A method for preparing a bismaleimide-based single-ion conductor polymer electrolyte membrane containing POSS, characterized in that: The following steps are involved: S1. Prepare a precursor solution I containing POSS and vinyl ethylene carbonate, and prepare a precursor solution II containing poly(vinylidene fluoride-hexafluoropropylene) and a single ion conductor monomer. The structural formula of the single ion conductor monomer is: S2, mixing the precursor solution I and the precursor solution II, adding a photoinitiator, and stirring at 20-30° C. to obtain a uniform slurry; S3, coating the slurry on a substrate, irradiating with ultraviolet light to initiate free radical polymerization, and drying to obtain an initial electrolyte membrane; S4. Fully immersing the initial electrolyte membrane in an electrolyte solution to obtain the electrolyte membrane.
2. The preparation method according to claim 1, characterized in that It also includes one or more of the following technical features: The mass ratio of A1, the single ion conductor monomer, POSS, vinyl ethylene carbonate, poly (vinylidene fluoride-hexafluoropropylene) and photoinitiator is 10: (0.5-2.2): (10-15): (5-7): (0.2-0.5); B1. The solvent in the precursor solution I or the precursor solution II is one or more of N,N-dimethylformamide, N,N-dimethylacetamide, N-methylpyrrolidone, isopropanol, and tetrahydrofuran; C1. The photoinitiator is one or more of 2-hydroxy-2-methyl-1-phenyl-1-propanone, benzoin diethyl ether, and benzoin dimethyl ether.
3. The preparation method according to claim 1, characterized in that It also includes one or more of the following technical features: A2, the ultraviolet irradiation is irradiation under 365nm ultraviolet light for 8 to 15 minutes; B2, the electrolyte is in accordance with V EC / V DEC =1 / 1 configuration of electrolyte.
4. A bismaleimide-based single-ion conductor polymer electrolyte membrane containing POSS, characterized in that: It is prepared according to the method according to any one of claims 1 to 3.
5. The electrolyte membrane according to claim 4, characterized in that The electrolyte membrane has a lithium ion transference number of 0.71 to 0.80 and a -4 S cm -1 Room temperature ionic conductivity.
6. A single ion conductor monomer, characterized in that The monomer structural formula is:
7. The method for preparing a single ion conductor monomer according to claim 6, wherein: The following steps are involved: The intermediate I and maleic anhydride are dissolved in a third solvent, reacted at 20-30° C. for 25-35 minutes, and then sodium hydroxide and acetic anhydride are added and reacted at 60-80° C. After the reaction is completed, ethyl acetate is added to produce a precipitate, and the precipitate is extracted to obtain the single ion conductor monomer. The intermediate I has the structural formula:
8. The method according to claim 7, characterized in that It also includes one or more of the following technical features: A3, the molar ratio of the intermediate I, maleic anhydride, sodium hydroxide, and acetic anhydride is 1:(2-3):(0.2-0.5):(6-7); B3. The third solvent is N,N-dimethylacetamide.
9. The method according to claim 7, characterized in that Dissolve p-nitrobenzenesulfonamide and lithium hydroxide in a first solvent, add p-nitrobenzenesulfonyl chloride at -5 to 5°C, and after sufficient reaction, extract the intermediate product; dissolve the intermediate product, palladium carbon catalyst and ferric chloride in a second solvent, add hydrazine hydrate at 60 to 80°C, maintain the temperature for reflux reaction for 3.5 to 4.5 hours, and extract the product to obtain the intermediate I.
10. The preparation method according to claim 9, characterized in that It also includes one or more of the following technical features: A4, the molar ratio of the three substances of p-nitrobenzenesulfonamide, p-nitrobenzenesulfonyl chloride and lithium hydroxide is 1:(1-1.2):(3-3.5); B4, the usage ratio of the four substances of p-nitrobenzenesulfonamide, palladium carbon catalyst, ferric chloride and hydrazine hydrate is 10g:(1-2)g:(0.5-2)g:(25-30)mL; C4, the first solvent is acetone; D4. The second solvent is anhydrous ethanol.